A cloudy planetary boundary layer oscillation arising from the coupling of turbulence with precipitation in climate simulations. (24th August 2017) - Zheng, X.; Klein, S. A.; Ma, H.‐Y.; Caldwell, P.; Larson, V. E.; Gettelman, A.; Bogenschutz, P.
Abstract: The Community Atmosphere Model (CAM) adopts Cloud Layers Unified By Binormals (CLUBB) scheme and an updated microphysics (MG2) scheme for a more unified treatment of cloud processes. This makes interactions between parameterizations tighter and more explicit. In this study, a cloudy planetary boundary layer (PBL) oscillation related to interaction between CLUBB and MG2 is identified in CAM. This highlights the need for consistency between the coupled subgrid processes in climate model development. This oscillation occurs most often in the marine cumulus cloud regime. The oscillation occurs only if the modeled PBL is strongly decoupled and precipitation evaporates below the cloud. Two aspects of the parameterized coupling assumptions between CLUBB and MG2 schemes cause the oscillation: (1) a parameterized relationship between rain evaporation and CLUBB's subgrid spatial variance of moisture and heat that induces an extra cooling in the lower PBL and (2) rain evaporation which happens at a too low an altitude because of the precipitation fraction parameterization in MG2. Either one of these two conditions can overly stabilize the PBL and reduce the upward moisture transport to the cloud layer so that the PBL collapses. Global simulations prove that turning off the evaporation‐variance coupling and improving the precipitation fraction parameterization effectively reduces the cloudy PBL oscillation in marine cumulus clouds. By evaluating the causes of the oscillation in CAM, we have identified the PBL processes that should be examined in models having similar oscillations. This study may draw the attention of the modeling and observational communities to the issue of coupling between parameterized physical processes. Key Points: This study identifies a cloudy PBL oscillation common to marine cumulus clouds in CAM with CLUBB and MG2 The oscillation is caused by deficiencies in the simplified coupling of turbulence with precipitation and deficiencies in the treatment of the precipitation evaporation This study demonstrates the importance of the coupling between parameterizations, which is often overlooked in climate model development